Some organization forms of differential teaching - Laužikas , J. (Psichologija, 1971)
Problems of differential teaching are widely discussed nowadays. Nobody doubts today that the all-round development of a creative personality is possible and depends on training of individual qualities of pupils’ aptitudes and interests. The article reviews some forms of differential teaching well known in other countries, namely: Manheim’s, Scharlottenburg’s, Vienna’s reforms and differential forms of teaching after World War II. Differentiation at schools has been carried out in Great Britain, the U.S.A., France, Sweden and Yugoslavia. Some forms of teaching differentiation at schools in socialist countries are mentioned in this article. Experiments of differential teaching in the U.S.S.R are discussed too.